LIABILITY OF MINORS FOR PROHIBITED ACTS IN POLISH LAW - Poniatowski, Piotr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: to describe the issue of liability of minors for acts prohibited under threat of punishment in Polish law. Research methods: the dogmatic-legal method was used (analysis of Polish normative acts), literature on the liability of minors for punishable acts was analysed, as well as statistical data relating to the research issue. Results: as a general rule, minors (i.e. persons who were under 17 years of age at the time of the act) are not criminally liable for acts that are punishable as crimes. The Polish Penal Code provides for exceptional criminal liability for certain crimes in the case of minors who were at least 15 or 14 years of age at the time of the act (Article 10 § 2 and 2a). On the other hand, minors are never criminally liable for acts prohibited as misdemeanours and fiscal offences (fiscal crimes or fiscal misdemeanours). Besides, minors who have committed an act punishable as a crime, a misdemeanour or a fiscal offence may be liable under the rules set out in the Act of 9 June 2022 on the Support and Resocialisation of Minors. The minor may then be subject to educational measures, a therapeutic measure and a corrective measure. Discussion: due to age restrictions, the range of crimes for which minors may be criminally liable, as well as other prerequisites for such liability provided for in Article 10 § 2 and 2a of the Polish Penal Code, minors are very rarely held criminally liable for acts prohibited as crimes. Minors who have committed a punishable act are mainly held liable in the family courts, but this is not criminal liability within the meaning of the Penal Code, the Misdemeanours Code and the Fiscal Penal Code. In general, the scale of minors’ delinquency in Poland has significantly decreased in recent years.